KONFLIK IDENTITAS SOSIAL MASYARAKAT TEMANGGUNG (Kajian Kekerasan Sosial di Temanggung Tahun 2011) - SUPARTO, DIRYO (Politika: Jurnal Ilmu Politik, 2012)
Abstract Social conflict that often occur in Indonesia today is always leads to social violence, vandalism, and arson.Â  Social violence that erupted after a five-year prison verdict against defendants charged with blasphemy by â€œ Antonius Raimond Bawengaâ€, gave a lesson to us all, that tringgers the conflict can be anything, anywhere, anytime.Â  Riot in Temanggung has provided clear evidence that social violence with various motif such as diverse as religious identity was sometimes still a problem that does not mess around.Â  It will be easily ignited by the sentiments of the true can very simple. If seen from the history of the conflicts in Indonesia, conflicts in the name of social identity --- ethnic, religious, racial, ethnic ---Â  often part and parcel of the nation.Â  According to Amien Maalouf (2004:9), why so may people comminting crimes in the present the name of religion, national, or various other identities.Â  Moreover, then one can do anything on behalf of their group identity. --- religious, ethnic, tribal, affinities --- which gas become a person in his life.Â  Or even the identity has been a guidance, doctrime and believed it could make a lot of people drain their energy and anger. Key ward : social conflict, identity, riot, inequalities, transformation,poverty,patron-client